Immune-Related Adverse Events and Their Association With the Effectiveness of PD-1/PD-L1 Inhibitors in Non-Small Cell Lung Cancer: A Real-World Study From China - Chen, Xiaoling; Nie, Jun; Dai, Ling; Hu, Weiheng; Zhang, Jie; Han, Jindi; Ma, Xiangjuan; Tian, Guangming; Han, Sen; Wu, Di; Wang, Yang; Long, Jieran; et al. (Frontiers in Oncology, 2021)
Background Programmed cell death-1/programmed cell death ligand-1 (PD-1/PD-L1) inhibitors are increasingly used in China, but no real-world data are available about the immune-related adverse events (irAEs). This real-world retrospective study aimed to assess the safety and effectiveness of PD-1/PD-L1 inhibitors in patients with non-small cell lung cancer (NSCLC) and to analyze the association between irAEs and effectiveness. Methods This was a retrospective study of the clinical data of patients with NSCLC treated with PD-1/PD-L1 inhibitors from August 2016 to November 2019 at Beijing Cancer Hospital. The patients were divided into the irAE or non-irAE groups. Overall adverse events, the impact of irAE on tumor response, and the association of irAEs with effectiveness were evaluated. Results One hundred and ninety-one patients were included, including 70 (36.6%) patients in the irAE group and 121 (63.4%) patients in the non-irAE group. AE, grades 3–5 AEs, and irAE occurred in 107 (56.0%), 24 (12.6%), and 70 (36.6%) of the patients, respectively. The objective response rate (ORR) and disease control rate (DCR) were higher in the irAE group compared with the non-irAE group (42.0% vs. 25.8%, P=0.038; 91.9% vs. 70.8%, P=0.002). Multivariable analyses identified that irAE were associated with progression-free survival (HR=0.62, 95%CI: 0.43–0.91; P=0.015), but not with overall survival (HR=0.76, 95%CI: 0.44–1.28; P=0.299). Conclusion In NSCLC treated with PD-1/PD-L1 inhibitors, patients with irAEs showed improved effectiveness over patients without irAEs. Future studies of anti-PD-1/PD-L1 immunotherapy should explore this association and the underlying biological mechanisms of efficacy.